Serum hCG Level and Rising World Health Organization Score at Second-Line Chemotherapy (Pulse Dactinomycin): Poor Prognostic Factors for Methotrexate-Failed Low-Risk Gestational Trophoblastic Neoplasia. Issue 8 (1st October 2010) - Kang, Woo Dae; Kim, Cheol Hong; Cho, Moon Kyoung; Kim, Jong Woon; Cho, Hye Yon; Kim, Yoon Ha; Choi, Ho Sun; Kim, Seok Mo
Abstract : Introduction: The aim of this study was to determine the factors associated with failure in patients receiving pulse dactinomycin as second-line chemotherapy for low-risk gestational trophoblastic neoplasia (GTN) according to the revised International Federation of Obstetrics and Gynecology 2000 scoring system at a single institution. Methods: Between January 1997 and June 2007, 37 patients with methotrexate-failed low-risk GTN were treated with pulse dactinomycin (1.25 mg/m 2 intravenously every 2 weeks). All patients had low-risk GTN based on the revised International Federation of Obstetrics and Gynecology 2000 scoring system at the time of second-line chemotherapy. A logistic regression model was used to analyze the relationship between covariates and treatment failure. Results: There were 28 (75.7%) patients who achieved primary remission with pulse dactinomycin. All 9 treatment failures achieved complete remission after receiving subsequent chemotherapy; 1 patient also underwent hysterectomy. Patients successfully treated with pulse dactinomycin required a median of 4.0 cycles (range, 2-7) to achieve a complete response. The risk of failure with pulse dactinomycin was higher for serum hCG levels 10 3 or higher when initiating pulse dactinomycin (odds ratio, 8.91; 95% confidence interval, 1.08-73.53) and a rising World Health Organization score of 2 or higher after first-line chemotherapy (odds ratio, 12.59; 95% confidence interval, 1.60-99.25). With respect to the previous methotrexate regimen and cause of failed methotrexate chemotherapy, there were no differences between those who were successfully treated and those who failed pulse dactinomycin. Conclusions: Serum hCG level and a rising World Health Organization score at the time of initiating pulse dactinomycin are important prognostic factors in patients with methotrexate-failed low-risk GTN receiving pulse actinomycin as second-line chemotherapy.